PVSET- CIES Graphic Interface. Quantification of the Degradation Index of Photovoltaic Systems (Global Journals of Research in Engineering, 2023)
The use of the Performance Ratio or global performance is a simple and effective method to evaluate the performance of photovoltaic grid connection systems Nevertheless there are theoretical reasons and experimental evidence that show that this parameter varies throughout the year by as much as 10 which prevents any value measured over a week from being considered representative of what occurs throughout the year The result presented Graphic interface PVSET-CIES contributes to the improvement of the efficiency indicators of the systems For this the procedure Quantification of the degradation index of the photovoltaic grid connection systems was developed which allows passively evaluating the degradation of the systems from the quantification of the degradation index The scientific novelty is based on the robustness of the coefficients used in the diagnosis against environmental conditions varying about 1 5 unlike the Performance Ratio procedure which varies up to 10 and the accuracy in terms of the model s prediction capacity used achieving a prediction error three times lower than the maximum power estimation model used in the Performance Ratio The graphical interface PVSET-CIES is supported in this procedure The tool provides information on energy losses and system degradation which serves as a prerequisite for decision makers for the development of maintenance and or repair programs that keep the system at optimum operating levels
Keywords: grid connected photovoltaic systems; procedure; performance ratio; graphic interface